2021
DOI: 10.18553/jmcp.2021.27.8.971
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medication nonadherence among Medicare low-income subsidy beneficiaries with diabetes, hypertension, and/or heart failure

Abstract: What is already known about this subject• The low-income subsidy (LIS) program was developed to offer financial assistance to Medicare beneficiaries with low income and assets by reducing their premiums and/or copayments.• Previous studies have identified factors associated with medication adherence and nonadherence, such as age, sex, race/ethnicity, and socioeconomic characteristics.• Less is known about the factors associated with medication nonadherence, specifically in the Medicare LIS population. What thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, these cross-sectional studies did not allow us to identify the mechanism for changes in disparities or to evaluate whether these changes were potentially causal. Another five studies considered interactions between a policy of interest (e.g., low-income subsidy eligibility) and race/ethnicity in the context of cross-sectional analysis or presented models stratified by policy (Biggers et al, 2016; Camacho et al, 2017; Roberts et al, 2023; Tsang et al, 2021; Zissimopoulos et al, 2015). These methods may have been better than stepwise models for understanding the impact of policy on disparities; however, they still could not account for unobserved differences across individuals grouped by policy eligibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, these cross-sectional studies did not allow us to identify the mechanism for changes in disparities or to evaluate whether these changes were potentially causal. Another five studies considered interactions between a policy of interest (e.g., low-income subsidy eligibility) and race/ethnicity in the context of cross-sectional analysis or presented models stratified by policy (Biggers et al, 2016; Camacho et al, 2017; Roberts et al, 2023; Tsang et al, 2021; Zissimopoulos et al, 2015). These methods may have been better than stepwise models for understanding the impact of policy on disparities; however, they still could not account for unobserved differences across individuals grouped by policy eligibility.…”
Section: Resultsmentioning
confidence: 99%
“…[53] Finally, patients residing in the West census region experienced a lower relative net benefit than those in Northeast region, possibly due to their lower rates of medication adherence compared to the Northeast region. [54] Caution should be exercised when interpreting the findings of this study, as there are several limitations to consider. First, certain patient-level socioeconomic characteristics that could affect the study outcome could not be evaluated, as the analysis primarily relied on information obtained from Medicare administrative data.…”
Section: Discussionmentioning
confidence: 95%
“…[ 53 ] Finally, patients residing in the West census region experienced a lower relative net benefit than those in Northeast region, possibly due to their lower rates of medication adherence compared to the Northeast region. [ 54 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the stepwise multivariable Cox regression analysis, young age and NICM were associated with a low compliance rate. Previously published data to define factors, which are associated with the likelihood of medication non‐adherence among Medicare low‐income subsidy recipients with type 2 diabetes, hypertension or heart failure showed that both young age and male gender are associated with low compliance 11 . Recently published descriptive data showed that the compliance rate regarding wearing a WCD is comparable in males and females 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…Previously published data to define factors, which are associated with the likelihood of medication non-adherence among Medicare low-income subsidy recipients with type 2 diabetes, hypertension or heart failure showed that both young age and male gender are associated with low compliance. 11 Recently published descriptive data showed that the compliance rate regarding wearing a WCD is comparable in males and females. 12,13 A further important aspect is that NICM is also associated with low compliance.…”
Section: Predictors Of Compliancementioning
confidence: 99%